The place of learning in a universal health coverage health policy process: the case of the RAMED policy in Morocco - E. Akhnif; J. Macq; Bruno Meessen (BMC, 2019)
Abstract Background To progress towards universal health coverage (UHC), each country will have to develop its systemic learning capacity. This study aims at documenting how, across time, learning can feed into a UHC policy process, and how the latter can itself strengthen (or not) the learning capacity of the health system. It specifically focuses on the development of a major health financing policy aligned with the UHC goal in Morocco, the RAMED, a health financing scheme covering hospital costs for the poorest segment of the population. Methods We conducted a retrospective analysis of the RAMED policy for the period between 1997 and 2018, along with a case study design. For the data collection and analysis, we developed a framework combining Garvin's learning organisation framework and the heuristic health policy analysis framework. We gathered data from key informants and document reviews. Results The study confirmed the importance of learning during the different stages of the RAMED policy process. There is evidence of a leadership encouraging learning, the introduction and adoption of knowledge management processes, and the start of a transformation of the administrative culture. Yet, our study also showed some major shortcomings, especially the lack of structure of the learning, and insufficient effort to systemise and sustain a transformation of practices within the health administration. Our study also confirms that the learning changes in nature across the different stages of the policy process. Conclusion The policy decisions and the implementation strategy create a learning dynamic, though not structured in all cases. Despite the positive interaction between learning and the RAMED policy, the opportunity to push forward a more structural transformation towards a learning system has not been fully seized. Hierarchical logics still largely prevail in the Moroccan health administration. The impact of future health policies for both the target beneficiaries and the health system will be bigger if their design integrates purposeful and structured actions in favour of organisational learning. This recommendation probably applies beyond Morocco.